Albuminuria in People Chronically Exposed to Low-Dose Cadmium Is Linked to Rising Blood Pressure Levels - Soisungwan Satarug; Supabhorn Yimthiang; Tanaporn Khamphaya; Phisit Pouyfung; David A. Vesey; Aleksandra Buha Đorđević (Toxics)
Exposure to low-dose environmental pollutant cadmium (Cd) increases the risks of both albuminuria and hypertension by mechanisms which are poorly understood. Here, multiple regression and mediation analyses were applied to data from 641 Thai subjects of whom 39.8%, 16.5%, 10.8%, and 4.8% had hypertension, albuminuria, diabetes, and chronic kidney disease (CKD), defined as the estimated glomerular filtration rate (eGFR) ≤ 60 mL/min/1.73 m2, respectively. To correct for interindividual differences in urine dilution and surviving nephrons, the excretion rates of Cd (ECd), albumin (Ealb), and β2-microglobulin (Eβ2M) were normalized to the creatinine clearance (Ccr) as ECd/Ccr, Ealb/Ccr, and Eβ2M/Ccr. The respective risks of having CKD and hypertension rose to 3.52 (95% CI: 1.75, 7.05) and 1.22 (95% CI: 1.12, 1.3) per doubling of the Cd body burden. The respective risk of having albuminuria increased 2.95-fold (p = 0.042) and 4.17-fold (p = 0.020) in subjects who had hypertension plus severe and extremely severe tubular dysfunction, defined according to the elevated β2M excretion rates. In multiple regression analysis, the Ealb/Ccr increased linearly with both the systolic blood pressure (SBP, β = 0.263) and diastolic blood pressure (DBP, β = 0.150), while showing an inverse association with eGFR (β = −0.180). The mediation model analyses inferred that a declining eGFR induced by Cd contributed to 80.6% of the SBP increment (p = 0.005), which then fully mediated an elevation of albumin excretion (p < 0.001). The present study provides, for the first time, evidence that causally links Cd-induced eGFR reductions to blood pressure elevations, which enhance albumin excretion.